Labour market prospects of Swiss career entrants after completion of vocational education and training - Salvisberg, Alexander [Verfasser]; Sacchi, Stefan [Verfasser] (My University, 2014)
"This study seeks to find the reasons for the rising risk of unemployment for people who have completed basic vocational education and training (VET) in Switzerland. We focus on the long-term structural shift on the demand side of the labour market and its consequences for new entrants' chances of employment in the labour force. A detailed analysis of the development of vacancies for such 'career entrants' in the time period 2001 to 2011 suggests that neither a growing occupational mismatch nor a general shift in the level of education to the disadvantage of workers with vocational education can be made responsible for the rising unemployment of labour market entrants. Instead, the available evidence indicates that a diminishing part of the vacancies suited for VET graduates remains open to entrants because of the increasing job requirements with regard to work experience and further education. Basic vocational education and training alone is increasingly less a guarantee for a smooth entry into the working world." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2 Arbeitsmarkt; G 1.2.3.2 Anforderungen & Bedarfe; I 2.2.1 Westeuropa; Berufseinmündung; Zweite Schwelle; Ausbildungsabsolvent; Berufsanfänger; Arbeitsmarktchance; Arbeitsmarktrisiko; Arbeitslosigkeit; Offene Stellen; Arbeitsplatzangebot; Qualifikationsanforderung; Schweiz